Acromial J-bone graft on the acromion for surgical treatment of glenohumeral instability: an anatomical study. Issue 4 (October 2017) - Sanchez, Matthieu; Klouche, Shahnaz; Faivre, Bruno; Bauer, Thomas; Hardy, Philippe
Background: Anterior glenohumeral instability is frequently associated with anteroinferior glenoid bone defects. One original technique has been described in the literature that incorporates a J-shaped graft from the iliac crest into the anterior glenoid rim. The main goal of the present study was to evaluate the feasibility of harvesting a J-shaped graft from the acromion that corresponds to previously described dimensions. The secondary goal was to determine the ideal harvesting site. Methods: Forty shoulders from 20 cadavers were included. Twenty grafts were harvested from the posterior acromion and 20 from the lateral acromion. The length, width and thickness of the grafts were measured. The incision was then enlarged to confirm the absence of an acromial fracture by fluoroscopic control. Results: Harvesting a graft whose size was similar to a J-graft was successfully performed in all cases (100%) with a mean (SD) incision of 4.2 (0.3) cm. Mean (SD) harvesting time was 4.5 (0.5) minutes. Two acromial fractures were identified during lateral harvesting (10%) and none during posterior harvesting ( p = 0.49). Conclusions: It is always possible to harvest a J-graft on the acromion. The posterior side of the acromion is the best site to harvest a graft that has the necessary size to treat glenoid bone defects.